High-intensity interval exercise improves cognitive performance and reduces matrix metalloproteinases-2 serum levels in persons with multiple sclerosis: A randomized controlled trial: - Zimmer, Philipp (Multiple sclerosis journal, 2017)
Background: Aerobic exercise can improve cognitive performance in healthy elderly people. Objective: The aim of this study was to investigate the influence of a...
Gesehen am 02.04.2020